DENR-MCT-1 promotes translation re-initiation downstream of uORFs to control tissue growth - Schleich, Sibylle; Straßburger, Katrin; Janiesch, Philipp Christoph; Koledachkina, Tatyana; Miller, Katharine K.; Haneke, Katharina; Cheng, Yong-Sheng; Küchler, Katrin; Stoecklin, Georg; Duncan, Kent E.; Teleman, Aurelio A. (Nature, 2014)
This study identifies the DENR-MCT-1 complex as the first factors in animals specific for translation re-initiation downstream of upstream Open Reading Frames (uORFs).